Parvovirus as a cause of hydrops fetalis: detection by in situ DNA hybridisation. Issue 4 (April 1988) - Porter, H J; Khong, T Y; Evans, M F; Chan, V T; Fleming, K A
Abstract : Lung tissue from 13 cases of unexplained non-immunological hydrops fetalis was examined by in situ hybridisation to detect parvovirus. Four specimens contained parvovirus DNA in cells in the blood vessel lumina and alveoli. Twenty six control cases were negative for parvovirus DNA. As there was no known epidemic of parvovirus infection during the study period, this suggests that parvovirus is a relatively common cause of non-immunological hydrops fetalis. In situ hybridisation may have a role in clinical medicine, particularly for retrospective investigations.